Sequential Morphological Changes in the CNV Net after Intravitreal Anti-VEGF Evaluated with OCT Angiography - Marques, JP (2016)
PURPOSE: To assess and describe sequential morphological changes in the choroidal neovascularization (CNV) net using optical coherence tomography angiography (OCTA) in patients undergoing treatment with intravitreal antivascular endothelial growth factor (VEGF). METHODS: Prospective cohort study. OCTA was performed sequentially: before (t0), 1 h (t1), 1 week (t2) and 1 month after the injection (t3), using Avanti RTVue XR equipped with the AngioVue® software (Optovue, Calif., USA). All images were classified by two independent graders. RESULTS: Ten eyes of 10 patients, with a mean age of 72.4 ± 10.5 years, were included. CNV morphology was described as tree-like in 5 eyes, glomerular in 1 and fragmented in 4. A fibrovascular capsule surrounding the CNV net was found in 4 eyes and a feeder trunk was noticed in 6. No changes were observed at t1. Loss of peripheral capillaries, vessel fragmentation and decreased vessel density were evident in 8 eyes at t2. The CNV capillary density and the peripheral anastomosis increased in all of these at t3. Two eyes remained unchanged through the whole length of follow-up. CONCLUSIONS: Significant changes in the CNV net can be observable in OCTA at least 1 week after intravitreal anti-VEGF. The safety of frequent examinations may provide a method of gauging treatment effects.